Late Turbidite Paradigm: Dispute on Cinambo Outcrop as Turbidites? - RMI Argakoesoemah (Ikatan Ahli Geologi Indonesia, 2001)
Conoco Indonesia performed a one-day geological fieldtrip to Majalengka and Kadipaten, West Java in late November 2000. The trip was led by DR. Dardji Noeradi (ITB).Discussion below is a short observation of the outcrops seen in Cinambo with no intention to describe or interpret the details of the outcrops. It should be noted here that the short timing and condition during the fieldtrip was insufficient to further dig out geology of the area in more scientific manner. However, some critical points have been identified, two of them are, in fact, basic questions arose during and after the fieldtrip completed: (1) is there any turbidite sediments in Cinambo, and (2) how the sequences seen were deposited.To respond to there crucial questions above one need further investigation and deep observation. It may take at least three or four months in the field just to prepare at least a couple dozen, correlatable detailed measured sections, observe and collect sedimentary structures, with no model-driven at all in mind. Other months are to work in the laboratory to record lithology variations and changes through possibly of hundreds of thin sections of systemtic rock samples. This is not a rocket science. But why? Here it is.